The role of brand self-relevance in developing brand loyalty: a study on the brand loyalty for Honda - A. Rahman, Nur Atikah; Md Noor, Shuhaida (School of Media and Communication Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2014)
This study investigates the role of brand self-relevance in developing brand loyalty on the automotive brand, Honda. In-depth interviews of 34 Honda owners in Malaysia were conducted. Those interviewed were asked on their feelings, experiences and loyalty towards Honda. The study conceptualised a research model combining Dick and Basu’s (1994) customer loyalty framework and Sirgy’s (1986) self-congruity theory. Results demonstrated there are two main self-relevance factors influencing consumers’ brand loyalty, which are product or brand user image congruity and need for self-expression. Specifically, study showed need of self-expression plays a significant role in influencing brand loyalty to portray consumers’ ideal, social and ideal-social self-images. Results also reveal brand self-relevance plays a significant role to both behavioural and attitudinal brand loyalty. Results illustrated brand self-relevance plays a more significant role in influencing consumers towards true loyalty than latent, spurious or no loyalty. This study suggests brand managers, advertisers and companies should focus on brand self-relevance in developing brand loyalty strategies to capture brand’s target market and retain them for a long duration of time. Findings provide a more specific direction in developing brand communication strategies and marketing plans to create strong and sustainable brand, retaining greater brand loyalty of the customers.